Avaliação do potencial neuroprotetor do beta-cariofileno em modelo murino de Doença de Parkinson induzido por 6-Hidroxidopamina - AMARAL, Anderson Valente (Universidade Federal do Pará, 2021)
Parkinson’s disease (PD) is classified as a motor disturbance characterized by resting tremor, muscular rigidity, postural instability and bradykinesia. These symptoms are caused by progressive loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) and consequently depletion of dopamine on striatum (STR). The search for new therapeutical approaches that may delay or interrupt the neurodegeneration in PD is essential to promote a better quality of life for patients. Thus, we investigated whether beta-caryophyllene (BCP) has neuroprotective effects in the 6-OHDA murine model of PD. Then, we performed behavioral tests such as apomorphine-induced rotations and exploration in the open field, we measured the optical density from STR fibers, quantified neurons and microglia in the SNpc through stereology and evaluated the total antioxidant capacity from STR and midbrain. Our evidence demonstrates that BCP reduced the degree of neurodegeneration induced by 6-OHDA, improved motor performance, protected striatal dopaminergic fibers, protected dopaminergic neurons and reduced microglial activation in the SNpc. But did not alter the antioxidant capacity in the STR and midbrain. Hence, BCP treatment has a potential neuroprotective effect in this mouse model of PD, which deserves to be better characterized for translational application.